2022
DOI: 10.1186/s12913-022-08454-9
|View full text |Cite
|
Sign up to set email alerts
|

The RE-AIM framework-based evaluation of the implementation of the Maternal and Child Health Handbook program in Angola: a mixed methods study

Abstract: Background The World Health Organization recommends the Maternal and Child Health Handbook (MCH-HB) to promote health service utilization from pregnancy to early childhood. Although many countries have adopted it as a national health policy, there is a paucity of research in MCH-HB’s implementation. Thus, this study aimed to evaluate the MCH-HB’s implementation status based on the RE-AIM framework (Reach, Effectiveness, Adoption, Implementation, Maintenance), and identify facilitators of, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Thus, inadequate supply of health care services and inputs, especially in rural areas are likely to be important constraints to the attainment of the continuum of care for maternal and child health in this study. To further elucidate barriers and facilitators to the intervention delivery, we did a mixed-methods implementation study which demonstrated the need for strengthening education for health care providers [ 27 ]. Our study also highlights the importance of health care provider training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, inadequate supply of health care services and inputs, especially in rural areas are likely to be important constraints to the attainment of the continuum of care for maternal and child health in this study. To further elucidate barriers and facilitators to the intervention delivery, we did a mixed-methods implementation study which demonstrated the need for strengthening education for health care providers [ 27 ]. Our study also highlights the importance of health care provider training.…”
Section: Discussionmentioning
confidence: 99%
“…Pre- and post-training assessments and direct observation revealed improvements in health care provider knowledge and competence in service delivery using the MCH handbook. However, urban/rural and facility level disparities in basic skills and competencies required for providing maternity services remain evident [ 27 ]. Evidence shows that health care provider training may further enhance availability and quality of maternity services when adapted to country needs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phases I and II projects formed the basis for the nationwide expansion of the MCH Handbook programme. We did an impact evaluation study from June 2019 to September 2020 to assess the programme impact on service use and MCH outcomes,17 while an implementation study that assessed the barriers and facilitators to the programme delivery done between October and November 2020 showed need to strengthen monitoring and supervision at healthcare facilities and training for healthcare providers 18…”
Section: The Mch Handbook Programmementioning
confidence: 99%
“…While there are many papers and reports of individual evaluations that used RE-AIM as an evaluation framework (7)(8)(9)(10)(11)(12)(13), and papers that use RE-AIM to synthesize information across multiple evaluations (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), fewer authors have addressed the utility of RE-AIM as an evaluation framework (25). The purpose of this manuscript is to capture one evaluation center's experience of using RE-AIM as an evaluation framework across a series of Enterprise-Wide Initiative evaluations.…”
Section: Introductionmentioning
confidence: 99%